ANALISIS PENGEMBANGAN INDUSTRI DI KABUPATEN BEKASI TAHUN 20102014 - Rr Nila Indrasari (KENEGARAAN, 2017)
This study analyzed the development of industry in Bekasi Regency 2010-2014, where the national industrial policy said about principle of industrial development policy should encourage industry growth and increased competitiveness of national industries. This study using descriptive analysis method, because researchers not only describes what is happening, but also explain why these problem happened. This study using secondary data for analysis and the secondary data is the data time series. Data analysis on this study using collaboration from descriptive method and secondary data analysis which is comparing data from year to year, business opportunities, sub-sectors and regions. Results of this study show that Bekasi District is an potential industry area and the industry has been developed, both in high-tech, medium, and low industries. Using of imported raw material in low and medium category of technology industry for production process is lower and decreased. With the development and deepening, and increasing of using local raw material will produce a strategic industry, increase the workforce and the value of industrial sector will be increase so the contribution of GDP in industrial sector in Bekasi District will be constantly increasing. With the development and deepening of industry in Bekasi District the public will get a great benefit. The role of government is ease to give permission and promoto the industries for using local raw material.Keywords: industrial policies, industrial development, deepening the industry